Asymmetric exchange is associated with P element induced male recombination in Drosophila melanogaster. - Duttaroy, A. (Heredity, 2002)
Spontaneous meiotic recombination events do not normally occur in the male germ line of Drosophila melanogaster. However, such events are induced in males when a P transposable element or a source of P element encoded transposase protein is present in its genome. This report concerns a molecular analysis of the meiotic exchanges that were induced in the male Drosophila by P elements within a genetically marked region of the third chromosome. The marked region also harbors a single P-element called P(lArB). Fifty-six percent of the P(lArB) region crossovers indicated some alterations in the P element 5' fragment. Such alterations appear to be related to asymmetric or unequal genetic exchanges. Finally, P(lArB) excision was found to be independent of P(lArB) region crossover events.